TINDAK PIDANA KESOPANAN DIBIDANG KESUSILAAN ( PERZINAHAN ) DALAM KUHP SERTA PADANANNYA DENGAN HUKUM PIDANA ADAT - Ida Bagus Made Danu Krisnawan (University of Udayana, 2015)
Adultery that in terms of customary criminal law known as drati karma a deviant act and violates decency offense under customary law. It is considered a serious offense and is a destructive act of moral and behavior that damages the harmony and balance, causing impure state (cuntaka). From the description that has been proposed, as for the formulation of the problem that arises in this paper is: